Quantum mechanics : the theoretical minimum - Susskind, Leonard (Susskind, Leonard. Theoretical minimum ;, 2015)
Explains the theory and associated mathematics of quantum mechanics, discussing topics ranging from uncertainty and time dependence to particle and wave states.--